PENDEKATAN ISLAM DALAM MEMELIHARA MASLAHAH WANITA SELEPAS KEMATIAN SUAMI - Syed Husin, Syh Noorul Madihah; Azahari, Raihanah (Jurnal Syariah, 2019)
A widow is a woman who has been left alone after the death of a husband who, supposedly, should be the one who acts as the breadwinner of the family. This group faces numerous obstacles and turbulence in order to survive after the death of their husbands. However, Islam has taken a comprehensive approach in order to protect the rights of the widow. This article will analyze and discuss the way of Islam in approaching the maslahah of a widowerr through the order of a waiting period (‘iddah), ihdad and Islamic inheritance. In addition, the explanation of the objective of syara’ and the wisdom behind the law will also be justified. It is concluded that the obligation of ‘iddah is a symbol of personal devotion to Allah and in honour to the former husband and his family. It also seeks to ensure the purity of consanguinity if the woman is pregnant during the waiting period (‘iddah). The obligation of ihdad is not the captivity of women but it is an emotional transition period and the preservation of the glory of a woman. In addition, Islam has given special privileges to the widow when listed as a beneficiary in the distribution of the inheritance of her former husband.